ʺTeamwork ability in the structure of professional competence of vocational education teachersʺ - Kovalskaya, V.; Нrankin, О. (Problems of Engineer-Pedagogical Education, 2024)
The article proves the necessity of educators possessing professional training in teamwork skills in the context of reforming the national educational system, one of the trends of which is the increase in constructive interaction and understanding among all participants in the educational process, effective collaboration with other educators and specialists in the field of education. According to the research results, the ability of educators in professional training to work in teams is identified as an integrated personal quality that includes a combination of knowledge, skills, abilities, and personal qualities regarding the formation and development of educational teams, diagnosing problems, and developing solutions aimed at improving the efficiency of teams formed by educators, learners, parents, and other participants in the educational process. The structure of the ability of educators in professional training to work in teams is distinguished, consisting of the following components: motivational (interest in teamwork, motivation for joint professional activities, desire for selfdevelopment), cognitive (knowledge of the theoretical foundations of team formation), activity (ability to form educational teams, distribute roles among team members, establish effective team communication, manage conflicts within the team), personal (qualities enabling effective teamwork: collective responsibility, activity, initiative, creativity, flexibility, harmonization of common goals with personal goals, situational leadership, constructive interaction, balance, readiness for change). It is established that the use of project methods, problem-based learning, role-playing games, and trainings in professional training contributes to the effectiveness of forming the mentioned ability, providing modeling of teamwork, simulation of situations of communicative interaction, and the development of team skills.